Scientific prospection of the application of Lean Manufacturing in occupational safety - Menezes, Michelle de Oliveira; Sant'Anna, Ângelo Márcio Oliveira; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2024)
The number of accidents has been growing over the years and this is also a reflection of management measures, which have more resources to map and identify the facts with diagnostic tools. Thus, implementing a management system based on occupational health and safety provides mechanisms, data accuracy for prevention and continuous improvement. The aim of the research was to apply a bibliometric study to identify the main publications in the field of lean manufacturing and occupational safety to map the main lean tools used and associate them with the requirements of NBR ISO 45001:2018. The method used was bibliometric research, between 2019 and 2024, using the keywords “Lean” OR “Lean Thinking” AND “safety” OR “ISO 45001” AND “industry” OR “manufacturing”. The results obtained were a greater predominance of conference articles, the country with the most publications were India and the most widespread tools were 5s, VSM and standardized work, with the item Operation of the standard having the highest frequency of correlation with lean tools. The research concludes that there are opportunities to explore the relationship between lean, safety and ISO 45001:2018, mainly due to the strategic relevance of both topics.
Keywords: lean manufacturing; safety; ISO 45001:2018